(untitled) (Ukrainian Journal of Ophthalmology, 2024)
The paper considers current views on the treatment of patients with neovascular glaucoma. Numerous treatments (ocular hypotensive medications, laser and surgical techniques and their combinations) have been attempted for intraocular pressure (IOP) control in NVG, but no consensus exists regarding the most effective medication or procedure. NVG requires emergency eye care, and its treatment is focused mostly on combating neovascularization and stabilizing the IOP. An advanced standardized multidisciplinary strategy for the management of patients with NVG is warranted to improve treatment outcomes for these patients. In patients with NVG, it is reasonable to use treatments aimed at (1) compensating for the underlying disease, (2) reducing retinal ischemia and neovascularization (such as panretinal laser photocoagulation and/ or anti-vascular endothelial growth factor (VEGF) therapy) and (3) lowering an abruptly elevated IOP (such as topical and systemic medical treatment and surgical and cyclodestructive procedures).